Factors Leading to Spelling Errors among and Their Impact on Acquiring Arabic Writing Skills at Al‑Amanah Modern Islamic Boarding School - Ahmad Zahuda; Yumanto, Mochammad Indra; Mamadou, Traore (Journal of Arabic Language Studies and Teaching, 2025)
This qualitative descriptive study examines the types, causes, and pedagogical implications of Arabic spelling errors among seventh-grade students at Al-Amanah Modern Islamic Boarding School, Junwangi–Krian, Sidoarjo. Data were obtained through classroom observations, semi-structured interviews, and diagnostic dictation tests, and analysed using thematic coding and error-percentage analysis. Findings reveal five major error categories: letter substitution or omission, misuse of solar and lunar “al,” hamza misplacement, confusion between tāʾ marbūṭa and tāʾ maftūḥa, and letter addition or deletion. These errors originate from phonological, morphological, cognitive, and affective factors, including weak phonological awareness, dialectal Arabic interference, cognitive overload, and low motivation. The study demonstrates that spelling accuracy strongly affects writing fluency and lexical quality. It contributes to Arabic L2 pedagogy by proposing an integrated framework that links phonological awareness with orthographic accuracy, emphasising the need for phonological–morphological training in a supportive, low-anxiety environment to improve Arabic writing competence.